Towards a practical theory for commercializing novel continuous living cover crops: a conceptual review through the lens of Kernza perennial grain, 2019–2022 - Cureton, Colin; Peters, Tessa E.; Skelly, Sophia; Carlson, Constance; Conway, Tara; Tautges, Nicole; Reser, Aaron; Jordan, Nicholas R. (Frontiers in Sustainable Food Systems, 2023)
As agricultural scientists rapidly develop and deploy novel continuous living cover (CLC) crops and cropping systems such as perennial grains, a growing number of intermediaries are engaged in advancing the commercialization, adoption, and scaling of these novel CLC crops. However, these commercialization practitioners lack a conceptual and practical roadmap to help them achieve success. Through key concept review and practice narratives, this article presents the firsthand experience of primarily non-academic staff at several key public and nonprofit agricultural innovation platforms between 2019 and 2022 that have held core institutional responsibilities for facilitating the commercialization, adoption, and scaling of Kernza® perennial grain, North America’s first commercially-viable perennial grain crop. Reviews of key concepts identified as relevant to the practice of commercializing novel continuous living cover crops are interwoven with practice narratives of the Kernza commercialization process through the lens of each concept, demonstrating the ways in which these concepts translate to specific activities, methods, and strategies, also noting remaining gaps, limitations, and areas for growth and learning. This narrative can move the growing community of CLC intermediaries and innovation brokers toward a ‘practical theory’ of CLC commercialization that lies at the intersection of technology transfer and adoption, innovation, and agri-food systems change processes. Such conceptual orientation and practical guidance stands to improve the efficacy of novel CLC crop commercialization intermediaries, accelerate wider efforts of agricultural innovation platforms to rapidly advance CLC agriculture, and provide fertile ground for further applied research.